2016
DOI: 10.1002/2015jb012470
|View full text |Cite
|
Sign up to set email alerts
|

Bimaterial effects in an earthquake cycle model using rate‐and‐state friction

Abstract: We have developed a computational framework to study earthquake cycles in 2‐D plane strain and apply it to faults separating dissimilar material. We consider a planar, strike‐slip fault governed by rate‐and‐state friction where quasi‐dynamic events nucleate spontaneously due to remote, tectonic loading. We investigate the influence of material contrast over the course of many hundreds of years. For the parameters we consider, we find that the presence of bimaterial properties influences the earthquake nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Simulations of bimaterial ruptures on an interface governed by slip‐weakening friction produced bilateral ruptures for various cases (e.g., Andrews & Harris, ; Harris & Day, ). However, large parameter‐space studies with slip‐weakening friction (e.g., Brietzke et al, ; Shi & Ben‐Zion, ), slip‐ and velocity‐dependent friction (Ampuero & Ben‐Zion, ) and rate‐state friction (Erickson & Day, ) showed that bimaterial ruptures tend to have preferred directivity for wide ranges of conditions. Recent high‐resolution laboratory experiments of bimaterial ruptures have led to the same conclusion (Shlomai & Fineberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of bimaterial ruptures on an interface governed by slip‐weakening friction produced bilateral ruptures for various cases (e.g., Andrews & Harris, ; Harris & Day, ). However, large parameter‐space studies with slip‐weakening friction (e.g., Brietzke et al, ; Shi & Ben‐Zion, ), slip‐ and velocity‐dependent friction (Ampuero & Ben‐Zion, ) and rate‐state friction (Erickson & Day, ) showed that bimaterial ruptures tend to have preferred directivity for wide ranges of conditions. Recent high‐resolution laboratory experiments of bimaterial ruptures have led to the same conclusion (Shlomai & Fineberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…The transitions in nonlinear rheology on fault surfaces, between rate weakening and rate strengthening, have been shown to contribute to the coseismic and interseismic slip evolution on the fault surface (Noda & Lapusta, ; Rice, ). However, off‐fault properties and bulk heterogeneities may also play a significant role in altering the earthquake cycle pattern (Cappa et al, ; Dolan & Haravitch, ; Erickson & Day, ; Lindsey et al, ). For example, ruptures that would load the bulk beyond its elastic limit, leading to the development of inelasticity or damage around the fault, may lock in nonuniform stresses on the fault surface that would impact subsequent ruptures (Erickson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of earthquake rupture in complex scenarios or involving earthquake sequences often use the so-called quasi-dynamic approach (Erickson & Day, 2016;Erickson & Dunham, 2014;Douilly et al, 2015;Rice, 1993;Rice et al, 2001;Wei et al, 2013), in which inertial effects are neglected. Slip instability under quasi-static mechanics leads to unbounded slip speeds, and the singularity is resolved through a radiation damping approximation, that is, by adding a velocity-dependent cohesion that bounds the slip velocity at rupture fronts (Rice, 1993;Rice et al, 2001).…”
Section: Introductionmentioning
confidence: 99%